Snow kissed [large type] - Thayne, RaeAnne (Center Point Large Print, 2026)
"'Tis the season for a little white lie . . . Christmas has always been single mom Holly Goodwin Moore's favorite time of year. The twinkly lights on the tree, the cookies in the oven, the snow on the ground. But she's just not feeling it this year. The wedding in her ex's family is almost here, her daughter, Lydia, is bursting at the seams to be a flower girl . . . and Holly couldn't be dreading it more. She told a little white lie about having a new boyfriend as her plus-one, hoping to save face. She needs a date for the wedding . . . and she needs it now. Ryan Caldwell wants to be free this holiday season. So even he isn't sure how he landed in Shelter Springs, looking after his niece, Audrey, with his estranged father down the road. But when he meets Holly, she makes him want to belong for the very first time. So they make a deal: he'll be her date if she'll help him give Audrey a true Christmas to remember while her mom is away."--